V2. Detection of epileptic activity in absence of EEG interictal epileptic discharges. Issue 8 (August 2015) - Pittau, F.; Genetti, M.; Birot, G.; Tomescu, M.; Baldini, S.; Vulliémoz, S.; Michel, C.; Seeck, M.
<x xml:space="preserve">Abstract</x> Rationale Aim: to assess if the EEGs of epileptic patients with any detectable spikes contain the voltage epileptic map, specific of the individual patient. Methods Fifteen patients with pharmaco-resistant focal epilepsy were included. Six minutes of EEG with spikes and six minutes without any detectable spikes were selected from long-term monitoring recording during wakeful resting state (EEG 31-channels, ref: FCz). Resting-state EEG from 48 healthy control subjects were also recorded and corrected for artifacts. For the EEG of each patient, we calculated the averaged spike and its voltage map. We fitted the spike map on (i) EEG of patient with visible spikes (ii) EEG of the same patient without any visible spike and (iii) EEGs of the 48 controls. The amount of presence of the voltage epileptic map was characterized using two criteria: mean correlation and Global Explained Variance (GEV). For these criteria statistical differences between (1) controls and EEG with spikes, and (2) controls and EEG without spikes were evaluated using z-scores. Results The patient-specific epileptic voltage map was significantly more represented in the spike-free EEGs of patients than in EEGs of healthy controls (GEV p = 0.029; mean correlation p = 0.032). This difference was more accentuated for the patient EEGs containing spikes (GEV p = 0.001, mean correlation (p < 0.001). Discussion Scalp EEGs of patients with pharmaco-resistant epilepsy contains the epileptic voltage map (index of epileptic activity), even in absence of any detectable interictal epileptic discharges. This finding suggests that epileptic voltage map could be a new epileptic bio-marker (SPUM grant 140332 and 141165).